The contest for North Sumatra Aceh, the Netherlands and Britain, 1858-1898 - Reid, Anthony (University of Malaya Press, 2017)
This book describes the painful transition of North Sumatra from a number of independent states to a part of Netherlands India (present day Indonesia).